The use of natural ingredient immunostimulants patterns for young men and women - Muhammad Rizki Jafar Kusdiawan; Fenny Yunita (Institute of Computer Science (IOCS), 2023)
The discovery of the first COVID-19 case in Indonesia, on March 2, 2020 in Depok causes people to use herbal products as an alternative to preventing COVID-19 for increasing the body's resistance. It has been widely found, immunostimulants play an important role in increasing our body's immunity. It is a substance thatacan strengthen or stimulate the immunessystem by interacting directly with active cells in the immune system. Immunostimulants from natural ingredients are an alternative with the same uses as immunostimulants. Apart from being relatively cheap, they are also easier to find because these are commonly used in everyday life. Plants that many people recognize to increase their immune system include: ginger, garlic, honey, meniran,. This studyyaims to determine the use of natural ingredients immunostimulants patterns in the community. The research methodology is descriptive with cross sectional design. This research was conducted to young men and women in the Pasir Buah Village with a total of 69 respondents. Dataawere collected by distributing questionnaires directlyzin December 2021 - January 2022. The results of the research that had been carried outybased on the questionnaire showed that out of 693respondents, 38 women respondents used natural ingredient immunostimulants, and 31 men respondents used natural product immunostimulants. Mostly respondents who used natural ingredients immunostimulants were women.